2020
DOI: 10.1029/2020jf005647
|View full text |Cite
|
Sign up to set email alerts
|

Probability Distributions of Particle Hop Distance and Travel Time Over Equilibrium Mobile Bedforms

Abstract: The joint probability distribution of streamwise particle hop distance, lateral particle hop distance, and travel time constrains the relationships between topographic change and sediment transport at the granular scale. Previous studies have investigated the ensemble characteristics of particle motions over plane bed topography; however, it is unclear whether reported distributions remain valid when bedforms are present. Here, we present measurements of particle motion over bedform topography obtained in a la… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 71 publications
1
12
0
Order By: Relevance
“…In the short‐term, particles over the dune tails perform bed‐load hops (e.g. Ashley et al ., 2020), with velocities that may be similar to those measured in this study for the same locations. In the long‐term, instead, one can expect that the sediment velocity and the dune celerity will be equal to one another, as clarified by a simple concept.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In the short‐term, particles over the dune tails perform bed‐load hops (e.g. Ashley et al ., 2020), with velocities that may be similar to those measured in this study for the same locations. In the long‐term, instead, one can expect that the sediment velocity and the dune celerity will be equal to one another, as clarified by a simple concept.…”
Section: Discussionsupporting
confidence: 80%
“…Ashley et al . (2020) instead took a Lagrangian approach to analyze the probability distributions of travel time and hop distances for bed‐load particles over equilibrium mobile bedforms; Wenzel & De Moraes Franklin (2019), finally, presented results for particle tracking over a barchan dune, that is a different case since it involves migration and lowering of an isolated sediment heap over a smooth bed. However, measurements of the bed‐load sediment motion over bed dunes are still extremely scarce, and frequently limited in space and time.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has also shown that sediment is dispersed in the cross-stream direction in the presence of dunes, which become more pronounced when dunes have a 3D character (Allen, 1982;Parsons et al, 2005;Reesink et al, 2018). By quantifying particle hop distance and travel time over equilibrium mobile dunes, Ashley et al (2020) showed that dunes significantly increase mean and standard deviation of cross-stream hop distances relative to a flatbed. As flow and sediment data in our study is limited to 2D slices through dunes which possess a 3D character from time to time, care must be taken while using this data as reference for modeling flow and sediment transport processes.…”
Section: Dune Slipface Angle and Flow Separationmentioning
confidence: 90%
“…The macroscopic (probabilistic) transport predictors of particle motion have not been tested for high Shields number (ϴ max = 0.12) (Ashley et al, 2020;Fathel et al, 2015;Furbish et al, 2012Furbish et al, , 2017Lajeunesse et al, 2010;Roseberry et al, 2012;Wu et al, 2020), with the exception of Ma et al (2014), thus showing a bias towards transport at low particle activity. Figure 5 provides important insights for extending the probabilistic theories towards conditions with high bedload particle activity.…”
Section: Implications For Sediment Transport Predictionmentioning
confidence: 99%